2014
DOI: 10.1186/1756-3305-7-405
|View full text |Cite
|
Sign up to set email alerts
|

Follow up of natural infection with Trypanosoma cruzi in two mammals species, Nasua narica and Procyon lotor (Carnivora: Procyonidae): evidence of infection control?

Abstract: BackgroundA large variety of mammals act as natural reservoirs of Trypanosoma cruzi (the causal agent of Chagas disease) across the American continent. Related issues are infection and parasite burden in these reservoirs, and whether they are able to control T. cruzi infections. These parameters can indicate the real role of mammals as T. cruzi reservoirs and transmitters. Here, two species of mammals, white-nosed coati (Nasua narica) and raccoon (Procyon lotor), were examined for to determine: a) T. cruzi pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
1
18
1
1
Order By: Relevance
“…These findings confirmed that T. cruzi transmission cycles are deeply immersed in the trophic nets. Additionally, differences in infectivity potential across the carnivore species have also been described the Procyonids, mainly N. nasua , N. narica and Procyon lotor , being the carnivore species that display the more expressive infectiveness potential as expressed by high and long-lasting parasitemias [ 3 , 27 , 47 49 ]. Note that Procyonids are omnivores that also feed on both insects and small mammals [ 50 ], a trait that enhances their chances of infection with the diverse T. cruzi DTUs.…”
Section: The Coati N Nasua and Other Carnivorementioning
confidence: 99%
“…These findings confirmed that T. cruzi transmission cycles are deeply immersed in the trophic nets. Additionally, differences in infectivity potential across the carnivore species have also been described the Procyonids, mainly N. nasua , N. narica and Procyon lotor , being the carnivore species that display the more expressive infectiveness potential as expressed by high and long-lasting parasitemias [ 3 , 27 , 47 49 ]. Note that Procyonids are omnivores that also feed on both insects and small mammals [ 50 ], a trait that enhances their chances of infection with the diverse T. cruzi DTUs.…”
Section: The Coati N Nasua and Other Carnivorementioning
confidence: 99%
“…Trypanosoma cruzi heterogeneity. The effects of T. cruzi infection are known to vary both between and within host species, 19,[32][33][34][35] and we observed the T. cruzi-infected C. lectularius life history response to be heterogeneous as well. This is consistent with the results from previous studies on the effect of T. cruzi on its hosts, both vertebrate and invertebrate.…”
Section: Discussionmentioning
confidence: 82%
“…Actually, in Mexico almost all DTU's have been depicted (DTUI, II-V), but the more frequently reported in humans and vertebrate reservoirs was the DTUI-which is probably the predominant across the country-while the others DTUs have been registered in invertebrate hosts [6][7][8][9][10]. There are a few exceptions in wild vertebrate hosts from southern Mexico, where DTUI and II have been identified [11,12].…”
Section: Introductionmentioning
confidence: 99%